LES BLOCAGES A L’AVENEMENT DE LA FINANCE VERTE DANS LE MONDE. - Guelord , TSHIBANGU MUSAFIRI; Barnabas, Ngongo Shindano; Terence, Et Lukama Lwamba (IJRDO - Journal of Business Management, 2023)
Drawn from a very recent past, green finance is an attempt to answer the thorny issue of climate change and the loss of biodiversity. Our readers will remember that the idea of setting up funds capable of compensating solution countries, protectors of their forests without which life on earth would become catastrophic,is a long-heard panacea,unfortunately,those who are supposed to crystallize it are sulky and do not have before them no coercive measures. Several issues and challenges must be taken up in order to finally hope to reach an agreement between the polluters and the coutries with solutions. The Cop 27 projected as a final meeting likely to remove any ambiguity seems rather a stillborn. As long as it does not have binding legal texts thus putting the polluters before their responsability, the impossible will be the green finance.